Penggunaan Prinsip Kesantunan Berbahasa Dalam Konteks Pembelajaran Siswa Kelas X Di SMA N 14 Medan - Elferina Y Siregar (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to describe the application of politeness principles in Indonesian language learning in the 10th grade at SMA N 14 Medan. The research population includes 360 10th-grade students from ten classes. A random sample was taken from classes X-1 and X-2, each consisting of 36 students. This study uses a qualitative method with a descriptive approach for data analysis. The results show that, based on politeness indicators, there are 80 polite data, 40 very polite data, 44 impolite data, and 5 very impolite data, with a total of 170 data points. The percentage of politeness level is calculated using the formula Ks =